Influence of Tryptophan Metabolism on the Protective Effect of Weissella paramesenteroides WpK4 in a Murine Model of Chemotherapy-Induced Intestinal Mucositis - Gabriele Moreira Guimarães; Karen Costa; César da Silva Santana Moura; Sarah Elisa Diniz Moreira; Joana Mozer Marchiori; Anna Clara Paiva de Menezes Santos; Rafaela Ribeiro Alvares Batista; Celso Martins Queiroz-Junior; Juliana Divina Almeida Raposo; Fernão Castro Braga; Marcelo Vidigal Caliari; Álvaro Cantini Nunes; et al. (Probiotics and Antimicrobial Proteins, 2025)

A question of rite—pearl millet consumption at Nok culture sites, Nigeria (second/first millennium BC) - Louis Champion; Alexa Höhn; Katharina Neumann; Gabriele Franke; Peter Breunig (Vegetation History and Archaeobotany, 2023)
The Nok culture in central Nigeria, dated 1500–1 cal bc , is known for its famous terracotta sculptures. We here present a study on > 11,000 botanical macro-remains from 50 sites, including 343 samples from Nok contexts and 22 samples dating between cal ad 100 and 400, after the end of the Nok culture. With 9,220 remains, pearl millet ( Cenchrus americanus (L.) Morrone, syn. Pennisetum glaucum (L.) R.Br.) is dominant in the Nok samples, followed by cowpea ( Vigna unguiculata (L.) Walp . ), Canarium schweinfurthii Engl., Nauclea latifolia Sm. (syn. Sarcocephalus latifolius (Sm.) E.A.Bruce), wild fruit trees and wild Poaceae. The pearl millet remains consist exclusively of charred caryopses; chaff remains are completely absent. Because we studied all size fractions, including the small 0.5 mm fractions usually containing the involucres, bristles and husks, the absence of pearl millet chaff is real, excluding a methodological explanation, and distinguishes Nok from contemporary other West African sites. We propose that most excavated Nok sites were consumer sites where clean grain was brought in from outside and consumed in a ritual context connected with feasting. This is in line with the archaeological evidence from the larger excavated sites with stone-pot arrangements that are interpreted as ritual places related to mortuary practices. In addition to the known southward branches of pearl millet diffusion from the Sahara we propose a new, hitherto unknown branch directly from the central Sahara to the central Nigerian savannas.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Making the invisible visible: tracing the origins of plants in West African cuisine through archaeobotanical and organic residue analysis - Julie Dunne; Alexa Höhn; Katharina Neumann; Gabriele Franke; Peter Breunig; Louis Champion; Toby Gillard; Caitlin Walton-Doyle; Richard P. Evershed (Archaeological and Anthropological Sciences, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Gene flow in admixed populations and implications for the conservation of the Western honeybee, Apis mellifera - Gabriele Soland-Reckeweg; Gerald Heckel; Peter Neumann; Peter Fluri; Laurent Excoffier (Journal of Insect Conservation, 2009)

Phenyl methyl ethers: novel electron donors for respiratory growth of Desulfitobacterium hafniense and Desulfitobacterium sp. strain PCE-S - Gabriele Diekert; Anke Neumann; Tina Engelmann; Roland Schmitz; Yvonne Greiser; Adelheid Orthaus (Archives of Microbiology, 2004)

Growth-Substrate Dependent Dechlorination of 1,2-Dichloroethane by a Homoacetogenic Bacterium - Stefaan De Wildeman; Anke Neumann; Gabriele Diekert; Willy Verstraete (Biodegradation, 2003)

A non-dechlorinating strain of Dehalospirillum multivorans : evidence for a key role of the corrinoid cofactor in the synthesis of an active tetrachloroethene dehalogenase - Anke Siebert; Anke Neumann; Torsten Schubert; Gabriele Diekert (Archives of Microbiology, 2002)

Tetrachloroethene reductive dehalogenase of Dehalospirillum multivorans : substrate specificity of the native enzyme and its corrinoid cofactor - Anke Neumann; Anke Siebert; Tina Trescher; Simone Reinhardt; Gert Wohlfarth; Gabriele Diekert (Archives of Microbiology, 2002)

Properties of tetrachloroethene and trichloroethene dehalogenase of Dehalospirillum multivorans - Anke Neumann; Gert Wohlfarth; Gabriele Diekert (Archives of Microbiology, 1995)

Isolation and characterization of Dehalospirillum multivorans gen. nov., sp. nov., a tetrachloroethene-utilizing, strictly anaerobic bacterium - Heidrun Scholz-Muramatsu; Anke Neumann; Michael Memer; Edward Moore; Gabriele Diekert (Archives of Microbiology, 1995)

Tetrachloroethene metabolism of Dehalospirillum multivorans - Anke Neumann; Heidrun Scholz-Muramatsu; Gabriele Diekert (Archives of Microbiology, 1994)